Pelatihan Pemanfaatan Jaringan Lan Dan Internet Kepada Perangkat Wali Nagari Gasan Gadang Kecamaatan Batang Gasan Kabupaten Padang Pariaman - Idwar Idwar; Yofina Mulyati; Syahrul Efend; Yentisna Yentisna; Enny Arita (LPPM Universitas Dharma Andalas, 2023)
The Wali Nagari device is one of the HR components that must be familiar with and able to utilize technological devices. The tasks he carries are very heavy including administering village government, development, and community affairs as well as assisting administration services to the Wali Nagari. With the ability to use information technology facilities in the form of sharing data, sharing printers, using e-mail and the internet, it is hoped that the internal coordination of village guardians can be better established. This service activity has relevance to the needs of the village guardian apparatus in Nagari Gasan Gadang at the Wali Nagari office. Based on the results of questions and answers with several levels of the nagari guardian during the visit of the lecturer team to the Gasan Gadang guardian's office. The wali nagari device has difficulties in sharing or sharing data and printers between colleagues in the wali nagari office. Another thing that is needed by the village guardian apparatus is the procedure for communicating on the internet using e-mail. By doing the service at the wali nagari gasan gadang office, it is hoped that the obstacles encountered can be overcome